Spontaneous spinal epidural hematoma developing after percutaneous coronary intervention: early diagnosis, early intervention, and good outcome - Ferhat Özyurtlu; Nurullah Çetin; Nihat Pekel; Mehmet Emre Özpelit (KARE Publishing, 2016)
A 56-year-old female patient hospitalized with diagnosis of acute coronary syndrome underwent early coronary intervention. Anticoagulant and antithrombotic treatment was administered, including acetylsalicylic acid, clopidogrel, and heparin in periprocedural period. Severe back pain and rapidly progressing paraplegia developed in early period of follow-up. The patient underwent surgery immediately after diagnosis of spontaneous spinal epidural hematoma (SSEH) causing pressure, and decompression was performed. The patient rapidly improved without recurrence through early diagnosis and early surgical intervention. A common problem encountered by interventional cardiologists is back pain in patients who have undergone interventions in the femoral region and have lain in the same position for an extended period. Clinical onset of SSEH includes similar complaints, a fact of which cardiologists should be aware. Early diagnosis and early intervention may provide a good outcome, as is reported in the present case.